Surface Modification of Nano-Silicon Nitride with Silane Coupling Agent - Wang, Xiaodong; Wan, Xinjun (Asian Journal of Chemistry, 2013)
In this work, a silane coupling agent was used for surface modification of native nano-sized silicon nitride (Si3N4) powder. According to the spectra of FT-IR and TGA, it can be inferred that this coupling agent covalently bonds on the surface of nano-Si3N4 particles and an organic coating layer was formed. The surface free energy experiments showed that the hydrophobic property of nano-Si3N4 modified with coupling agent was improved obviously. Analysis of nanoparticle size and TEM revealed that the modified nano-Si3N4 possessed good dispersibility and the average diameter was less than 100 nm.